On One Possibility to Improve Reliability of Magnetic Starter - V. A. Anishchenko; A. G. Maystrovich; A. V. Lesota (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes and considers a possibility to improve an operational reliability of reversing magnetic starters by reservation of main and auxiliary contacts in accordance with majority-logic voter «two out of three».